Development and Validation of a Scale on Religious Satire Memes and Muslim Youth Identity in Online Communities - Zakiyyah Wardatul Laini; Eti Efrina; Juni yanti; Syukri Amin; Fransiskus Novrianto Pakpahan (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
The contemporary digital landscape has created new arenas for the negotiation of religious values, with internet memes serving as a dominant tool for social satire and critique. In this context, the present methodological study aims to develop and conduct an initial validation of a scale measuring exposure to religious satire memes, attitudes toward religion, and Muslim youth identity in online communities. Employing a quantitative approach, primary data were collected through a closed-ended online questionnaire administered to 200 respondents selected via purposive sampling from a population of 215 individuals. The psychometric evaluation focused on item validity using product–moment correlation analysis. Of the 27 statement items initially constructed, only 17 met the validity criterion (r-count > r-table 0.1388), whereas 10 items—including several within the Attitude toward Religion (SA) and Muslim Identity (IM) dimensions—were found to be invalid due to negative or near-zero correlation values. Given the substantive proportion of invalid items, the research was intentionally concluded at the validity testing stage to avoid generating misleading findings from a flawed measurement instrument. These results indicate that the current version of the scale cannot yet be used for hypothesis testing or inferential analysis regarding the relationships among the constructs. The primary implication is the need for systematic revision of the invalid items, potential reconceptualization of specific dimensions, and subsequent pilot testing to obtain a more robust and psychometrically sound instrument for future studies on religious satire memes and Muslim youth identity in online environments.